Perdamaian Agama Di Negeri Plural (Studi tentang Praktik Dialog Antar-Agama di Indonesia perspektif Komunikasi Antarbudaya) - Faiz Tajul Millah (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2010)
This research aims to examine religious harmony in Indonesia from the end of Soekarno’s rule up to the reformasi era, to identify the factors causing the government’s failure to keep the religious harmony, and to know how interfaith institutions in Jogjakarta work to create religious harmony in society. This is a descriptive, comparative, and qualitative research because the data are collected from books, documents, and interviews, then used in a comparative analyze.The interfaith institutions examined are limited to only two institutions, Interfidei and FPUB.  The research findings show that attempts to realize religious harmony should not be dominated by government, but the role of society itself are very significant. The role of society represented in NGO work is a more bottom-up approach to solve the problems in society.  Their work is the antithesis of government approach.  However, not all of the interfaith institutions have the same method to work.  Although they work based on real problems of society, they use different ways to interact with them.  Interfidei and FPUB are examples of this.  Interfidei uses a more elite approach to contact with society.  FPUB uses a more non-elite approach, based on the grassroots level of society.  Those two types of contacts each have strengths and weaknesses, so the two organizations complement each other.  The best method would be if there was an NGO that could combine both ways, although it would be very difficult.